Penerapan Media Puzzle Gambar Berseri Berbasis PjBL untuk Meningkatkan Keterampilan Menulis Teks Narasi pada Siswa - Rahmah, Meily Aulia; Agustina, Putri; Khikmah, Nurul; Suryani, Eva Dwi; Puwati, Panca Dewi (Lembaga Yasin AlSys, 2025)
The narrative writing skills of first-grade students at SDN Blerong 2 remain relatively low, as indicated by difficulties in organizing storylines, developing ideas, and coherently connecting pictures to sentences, thereby necessitating instructional innovations that actively and concretely engage learners. This study aims to describe the implementation of a sequential picture puzzle medium based on Project-Based Learning (PjBL) and to examine its effectiveness in improving first-grade students’ narrative text writing skills at SDN Blerong 2. A mixed-methods design combining quantitative and qualitative approaches was employed with 27 students, using narrative writing skill tests administered as pretests and posttests, alongside classroom observation of learning activities. The results show that at the pretest stage most students were in the “fair” category (55.6%), followed by the “poor” category (22.2%), and only 7.4% reached the “very good” category. Following the implementation of project-based learning using sequential picture puzzle media, posttest results improved significantly, with 74.1% of students in the “very good” category, 22.2% in the “good” category, and no students remaining in the “poor” category. These findings indicate that sequential picture puzzle media based on PjBL effectively support students in understanding storylines, linking images with words, and writing coherent and complete narratives. Accordingly, project-based learning using sequential picture puzzles is proven effective in enhancing first-grade students’ narrative writing skills and can serve as an innovative instructional strategy for elementary school teachers to improve the quality of active and meaningful writing instruction.